A performance of ingenuity research using bibliometric method - Ali, Azharudin (Blue Eyes Intelligence Engineering & Sciences Publication, 2019)
The age of fast modifications across the digital and new technology-driven economy, artificial intelligence, and fast cycles of product life have made engineering important for worldwide economic and social development. Further, ingenuity is also crucialinconfronting the uncertainties and challenges brought byIndustrial Revolution 4.0 (IR4.0) and dynamic businessenvironment.Hence, this studyaims to analyze and look atthetitleof papersand articles on the ingenuity studies derived from Scopus database. By and large, ingenuity is defined as“the quality of inventive, original andnovelty”, This means an intrinsic or inborn skill for practical ideas, intelligence, ingenuity, creativity, and the ability to innovate, solve issues, and generate fresh stuff and ideas. In this study, the coverage we reviewed on ingenuity titles includes multidisciplines and regions from the entire perspective of ingenuity studies, not limited to the ingenuity of technology, science, production and engineering.Thus, it providesa profile and insights into the behavioursand attributesof the ingenuity study to discovera title of publications and researchevidenceor expectednessthat possibly will occur in papers.Data are collectedemployinga bibliometric approach to analyze the titles of papers, research and publications that have been listed and indexed by Scopus(exclude the publicationyear 2018). Therefore, all articles fromvarious type of documents and sourcesthat have ingenuity keyword in its title including author keywords and abstracts in the Scopus databasehas been obtained and analyzed.The result showsa total of 465 papers are obtainablefor further analysis after carrying out the cleanup process. Furthermore, it indicatesabout 75 percent or 346 out of 465 articles came from journals source type that has the ingenuity keywords in its.The outcomes of this bibliometric analysisarefound to be usefulfor researchersin providing valuable insight and understanding about the prospect and outlook of the global research on ingenuity as well as in finding future research direction.